Does Electrification Spur the Fertility Transition? Evidence from Indonesia - Michael Grimm; Robert Sparrow; Luca Tasciotti (Institute for the Study of Labor (IZA), 2014)
We analyse various pathways through which access to electricity affects fertility, using a pseudo-panel of Indonesian districts covering the period 1993-2010. Identification of causal effects relies on a district-fixed effects approach and controlling for local economic development. The electrification rate increased by about 65 percent over the study period and our results suggest that the subsequent effects on fertility account for about 18 to 24 percent of the overall decline in the fertility rate, depending on the specification. A key channel through which electrification affects fertility is increased exposure to TV, explaining about a quarter of the total fertility effect. Using in addition several waves of Demographic and Health Surveys, we find suggestive evidence that increased exposure to TV affects in particular fertility preferences and increases the effective use of contraception. Reduced child mortality seems to be another important pathway linking access to electricity and fertility. We find no evidence that changes to direct and indirect costs of children play a role. Overall, the results suggest that electrification contributes substantially to the fertility decline. In a context in which family planning policy still plays an important role this second order effect should be taken into account in cost benefit analyses of publicly funded grid expansion policies.
Keywords: H43; H54; J13; J22; O18; Q40; 330; fertility; fertility transition; electrification; family planning; television; infrastructure; child mortality